Implementasi Projek Penguatan Profil Pelajar Pancasila Tema Kewirausahaan di SDN Wangiwisata Kabupaten Bandung - Rendrapuri, Rezy Vianthia; Salsabilla, Heidi Giva; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2023)
The implementation of the Independent Curriculum which then gave birth to the Project for Strengthening the Profile of Pancasila Students (P5), which is still relatively new, raises question marks for schools about how to implement it. This research aims to find out how SDN Wangiwisata Bandung implements the Project for Strengthening the Profile of Pancasila Students from planning to evaluation and this research is expected to provide an overview of the project activities for strengthening the profile of Pancasila students for elementary school teachers. Apart from that, it is hoped that it can provide opportunities for other researchers in take a relevant theme. This research uses descriptive qualitative methods by means of direct observation and interviews with school principals and teachers at SDN Wangiwisata. From the research, it was concluded that overall, the implementation of P5 carried out at SDN Wangiwisata applies 3 dimensions cooperation, creative, and critical reasoning